Exposure and response (ritual) prevention for obsessive-compulsive disorder : therapist guide - Foa, Edna B.; Yadin, Elna; Lichner, Tracey K. (Treatments that work., 2012)
Designed to be used in conjunction with its companion online patient workbook, this Therapist Guide includes supporting theoretical, historical and research background information, diagnostic descriptions, differential diagnoses, session by session treatment outlines, case examples, sample dialogues, practice assignments, and tailored application to the vast variety of presentations and nuances of the disorder.